DNA Barcoding of Cardinalfish (Apogonidae) in Gilimanuk Bay, Bali, Indonesia - Putra, I Nyoman Giri Putra; Indrawan, Gede Surya; Faiqoh, Elok (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Abstract The Apogonidae is estimated to consist of nearly 300 fish species, most of which inhabit coral reef areas. The lack of distinctive body markings and overlapping species distribution makes species assignment challenging. Therefore, this study aimed to delineate species and establish barcoding reference databases of Apogonidae in Gilimanuk Bay (Bali, Indonesia) using the Cytochrome Oxidase I (COI) gene of the mitochondrial DNA. A total of 22 fish tissue samples were extracted with 10% Chelex solution. BLAST analysis was performed and genetic differentiation between species was calculated. The phylogenetic tree was constructed using the Maximum Likelihood method and tree visualization was generated using iTOL V5. The morphology and genetic identification results based on the mitochondrial COI gene revealed eight species of seven genera, and one species was new to GenBank online database. This study was the first-ever addition of COI sequence for Ostorhinchus hartzfeldii into the GenBank database. The average K2P genetic distance within species and K2P distance between genera within the family were 0.60% and 19.10%, respectively. The mean genetic distance between genera within the family was 31.8-fold higher than the mean genetic distance within species. The phylogenetic tree showed that each sample resided in a distinct cluster, which indicates that DNA barcoding is a reliable and effective approach for species delimitation in Apogonidae fishes. Highlight Research Eight species of cardinalfish in Gilimanuk Bay were delineated using the barcoding method. This study provides the first nucleotide sequence for Ostorhinchus hartzfeldii in GenBank online database. The phylogenetic tree showed that each sample resided in a distinct cluster, indicating that the barcoding method efficiently differentiated at the species level. The mean genetic distance between genera within the family was 31.8-fold higher than the mean genetic distance within species.